(untitled) (Ameghiniana, 2014)
"Four species of the subfamily Elythinae (Brachiopoda) from different localities of Precordillera and Cordillera Frontal in San Juan and Mendoza provinces are identified. Other occurrences of this subfamily from Patagonia, including an undetermined species of the genus Spirelytha Fredericks, are described and figured. Kitakamithyris booralensis (Campbell) and Torynifer sp. of La Capilla Formation of Namurian age (Levipustula Zone); and Kitakamithyris immensa (Campbell) and Torynifer tigrensis sp. nov., of the Yalguaraz Formation, assigned to the Westphalian, are likewise described and figured. Kitakamithyris booralensis and K. immensa are added to the common faunal elements between Argentina and Australia during the late Palaeozoic."